1988
DOI: 10.1007/bf00378695
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study on the hepatotoxicity of occupational toluene exposure

Abstract: In a cross-sectional study of 181 male workers of a rotogravure printing plant, most of whom were exposed to toluene levels well above the GDR threshold limit values, 55 subjects revealed pathological liver screening values (activities of serum aspartate aminotransferase, alanine aminotransferase, gamma glutamyltransferase; liver size). The differential diagnostic examination showed in 51 out of these 55 subjects an association with competing factors such as alcohol abuse (78%) and overweight (40%), to a sligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Although the hepatotoxic eff ects of various organic solvents are ordinarily regarded as already established, a causal connection between toluene inhalation and liver injury is still controversial (Boewer et al, 1988;Dossing et al, 1983;Guzelian et al, 1988;Howell et al, 1986;Morris, 1989), and these inconsistent results existing in relation to the hepatotoxic eff ect of toluene inhalation can be explained as a consequence of diff erences in the exposure conditions, and also considered to be attributed to the diff erent sensitivity in examining the liver injury (Franco et al, 1986). In the present study, to detect the early stage of hepatotoxic changes, the immunohistochemical analyses of histological markers for hepatic fi brosis were then carried out, and the expression of both a-SMA and collagen in the liver was shown to be clearly enhanced by exposing the animals to toluene vapor (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the hepatotoxic eff ects of various organic solvents are ordinarily regarded as already established, a causal connection between toluene inhalation and liver injury is still controversial (Boewer et al, 1988;Dossing et al, 1983;Guzelian et al, 1988;Howell et al, 1986;Morris, 1989), and these inconsistent results existing in relation to the hepatotoxic eff ect of toluene inhalation can be explained as a consequence of diff erences in the exposure conditions, and also considered to be attributed to the diff erent sensitivity in examining the liver injury (Franco et al, 1986). In the present study, to detect the early stage of hepatotoxic changes, the immunohistochemical analyses of histological markers for hepatic fi brosis were then carried out, and the expression of both a-SMA and collagen in the liver was shown to be clearly enhanced by exposing the animals to toluene vapor (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, most organic industrial solvents are considered to be toxic, and hence induce damage to the liver, resulting in fatty liver, hepatomegaly and cirrhosis. However, despite considerable eff orts to elucidate the hepatotoxic eff ects of toluene and its derivatives, it seems still controversial whether the exposure to these substances may actually induce substantial damage to the liver in the factory workers (Boewer et al, 1988;Dossing et al, 1983;Guzelian et al, 1988;Howell et al, 1986;Morris, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The findings show that the screening protocol employed is valid and easily administered in the workplace to identify subjects at risk of hepatotoxicity, detecting risk among an exposed population and establish how often tests should be done, depending on the level of response of the variables investigated [21][22][23][24][25][26][27][28][29][30]. Disinfestation workers should therefore undergo periodic health checks with particular attention paid to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…The numbers of individuals exposed to it are therefore very large. The solvent is considered to have only low toxicity (Brucker et al 1981;Boewer et al 1988), but a number of investigations have shown that toluene exposure can result in pathological and biochemical changes in liver, central nervous system and other organs, both in people exposed to toluene (O'Brien et al 1971;Guzelian et al 1988) and in animal experiments (Rea et al 1984;Rees et al 1987;Hsieh et al 1989). The biological monitoring of individuals exposed to toluene is very important in evaluating the extent of exposure, but it remains in question which urinary metabolite, hippuric acid (HA) or o-cresol, is better as an index of expoure.…”
Section: Introductionmentioning
confidence: 99%